Analysing the dynamic relationship of land surface temperature and landuse pattern: A city level analysis of two climatic regions in India - Dipendra Nath Das; Suman Chakraborti; Gourab Saha; Anushna Banerjee; Dharmaveer Singh (City and Environment Interactions, 2020)
Intense urbanization in the Indian cities has brought about phenomenal changes in the existing landuse patterns, whereby increasing trends of surface temperature and the presence and absence of green cover and water bodies, their shape, pattern, configuration significantly modifies the thermal properties of the city. The present study comprehendeds how different biophysical, anthropogenic, and landscape composition determine and interact with the surface temperature in different climatic zones in India, by taking Jaipur and Guwahati cities as examples. This study has also incorporated several landscape metrics of composition and configuration and spatial cluster analyses to identify the most fragmented landscape in the two cities. Such complex relationship among the landuse and landcover, bio-physical parameters and the surface temperature can be assessed by using the Generalised Additive Model (GAM). Result shows that Jaipur has experienced high temperature changes in city centre in comparison to Guwahati, which can be attributed to the differential presence of environmental sensitive land class in the city cores and peripheries. Results also indicate that medium patches of environmental sensitive land class, as well as close proximity and configuration with environmental non-sensitive class reduces the surface temperature in two heterogenous landscape. Thus, Policymakers and urban planners could be assisted by our finding to mitigate surface temperature in the city.